Upregulating mTOR/ERK signaling with leonurine for promoting angiogenesis and tissue regeneration in a full-thickness cutaneous wound model. Issue 4 (28th March 2018) - Wang, Chenggui; Zhang, Zengjie; Xu, Tianzhen; Lou, Yiting; Wang, Qingqing; Jin, Haiming; Zhang, Lilian; Feng, Yongzeng; Xu, Huazi; Mao, Cong
Abstract : LN promoted the angiogenesis of endothelial cells by activating the mTOR/ERK pathway, and efficiently enhanced the wound-healing process in vivo . Abstract : Wound therapy remains a clinical challenge due to the poor vascularization during the healing process and the high demand to achieve functional and aesthetically satisfactory scars. Newly-formed blood vessels are necessary for wound healing since they can deliver nutrients and oxygen to the wound area. In this study, the role of leonurine (LN), a traditional Chinese medicine isolated from Herba leonuri, in promoting angiogenesis and its function in wound healing have been investigated. The results of co-culture with human umbilical vein endothelial cells (HUVECs) demonstrated that LN treatment (5–20 μM) could promote the proliferation and migration and enhance the ability of in vitro angiogenesis through up-regulating the mTOR/ERK signaling pathway. Furthermore, a full-thickness cutaneous wound model was used to investigate the healing effect of LN in vivo . Intragastric administration of 20 mg per kg per day LN stimulated the regeneration of more blood vessels at the wound sites, which confirmed the in vitro results of promoting angiogenesis. Due to fast vascularization, the collagen matrix deposition and remodeling processes were also accelerated in LN treated wounds, resulting in efficient wound healing. In summary, LN promoted angiogenesis of endothelial cells in vitro by activating the mTOR/ERK pathway, and could efficiently enhance the angiogenesis and collagen deposition of the regenerated tissue, together with facilitating the wound healing process in vivo . This study provides evidence for LN-stimulated angiogenesis and tissue regeneration in skin wounds, especially in ischemic wounds.